2012
DOI: 10.1146/annurev-nutr-071811-150630
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes in Asians: Prevalence, Risk Factors, and Effectiveness of Behavioral Intervention at Individual and Population Levels

Abstract: This review summarizes the current data on diabetes risk factors, prevalence, and prevention efforts in Asia and Asian migrant populations. Studies indicate that type 2 diabetes mellitus is a large and growing threat to public health in Asian populations. Furthermore, Asian subgroups (e.g., South Asians/Asian Indians, Chinese) have unique risk factor profiles for developing diabetes, which differ from other populations and between Asian ethnic groups. Lifestyle intervention programs are effective in preventing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 159 publications
(172 reference statements)
1
49
0
Order By: Relevance
“…39 Such estimates are broadly comparable with ours, the lower estimate for Asia being likely caused by a lower prevalence of diabetes in those populations. 40 Heavy alcohol drinking, but not low to moderate consumption, has been associated with an increased risk of pancreatic cancer. [17][18][19] A meta-analysis of 21 case-control and 11 cohort studies reporting a 22% excess risk for pancreatic cancer for heavy drinkers (≥3 drinks per day) indicated that only 2% to 3% of all pancreatic cancer cases could be attributed to alcohol consumption in a population with 10% to 15% of heavy drinkers.…”
Section: Discussionmentioning
confidence: 99%
“…39 Such estimates are broadly comparable with ours, the lower estimate for Asia being likely caused by a lower prevalence of diabetes in those populations. 40 Heavy alcohol drinking, but not low to moderate consumption, has been associated with an increased risk of pancreatic cancer. [17][18][19] A meta-analysis of 21 case-control and 11 cohort studies reporting a 22% excess risk for pancreatic cancer for heavy drinkers (≥3 drinks per day) indicated that only 2% to 3% of all pancreatic cancer cases could be attributed to alcohol consumption in a population with 10% to 15% of heavy drinkers.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 Diabetes Mellitus (T2DM) is a multifactorial disease involving both genetic and environment factors [1]. Diabetes mellitus is generally classified into 4 groups based on their pathogenesis with T2DM as the most frequent group (90-95%).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the rapid growth of the Non-Hispanic Asian population in the U.S., the urgent need of assessing metabolic dysfunction in this population also lies in the observation that Non-Hispanic Asian populations around the world are at increased risk for metabolic symptoms that may contribute to the development of type 2 diabetes [7,8] . Cross-sectional studies that compare Non-Hispanic Asian populations to other racial/ethnic groups in North America suggest that Non-Hispanic Asians experience an elevated prevalence of metabolic risk relative to other racial/ethnic groups [9][10][11] . Nativity to the U.S. has important effects on the development of metabolic dysfunction and type 2 diabetes among Non-Hispanic Asians.…”
Section: Introductionmentioning
confidence: 99%